Sensations, Evergreens in the Media and Social Memory: Watergate Scandal, 9/11 and Others as Places and Milieus of Remembering - Fokas, Nikos; Kopper, Ákos (Szociológiai Szemle, 2023)
This paper offers a longitudinal analysis of media dynamics and aims to capture the media as the vehicle of collective memory in modern societies. Associating the media with memory, however, sounds paradoxical, given that the media is usually associated with novelty and actuality. We argue that parallel to its topicality, the media also creates communities of remembering in modern societies. Hence, we suggest that what Pierre Nora called milieus of memory are not lost in modernity, but merely moved from the realm of interpersonal interactions to the space of the mediated reality of the media. Furthermore, we argue that these milieus of memory frequently evolve into what Nora called places of memory.